2018
DOI: 10.1103/physrevd.98.014033
|View full text |Cite
|
Sign up to set email alerts
|

Influence of vector interactions on the favored shape of inhomogeneous chiral condensates

Abstract: We update a previous study of the effects of vector interactions in the Nambu-Jona-Lasinio model on the formation of inhomogeneous chiral symmetry breaking condensates. In particular, by properly considering a spatially modulated vector mean field associated with the quark number density of the system we show that, as the value of the vector coupling increases, a chiral density wave modulation can become thermodynamically favored over a real sinusoidal modulation. This behavior is found both via a GinzburgLand… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Finally, we recall that, while our analysis focused on the lowest-order GL coefficients which are relevant for pinpointing the location of the CP and the (P)LP, it would also be interesting to work out higher-order coefficients, as they can give informations on the favored shape of the spatially modulated chiral condensate [16,17], as well as determine the phase boundary to the chirally restored phase [18].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we recall that, while our analysis focused on the lowest-order GL coefficients which are relevant for pinpointing the location of the CP and the (P)LP, it would also be interesting to work out higher-order coefficients, as they can give informations on the favored shape of the spatially modulated chiral condensate [16,17], as well as determine the phase boundary to the chirally restored phase [18].…”
Section: Discussionmentioning
confidence: 99%
“…We investigated both Ansätze because in previous similar studies as in Refs. [1,2], the CDW has been used, but since then it has been found that the RKC is in most cases energetically preferred over the CDW Ansatz [8,23], at least for vanishing vector interactions [32].…”
Section: Resultsmentioning
confidence: 99%
“…There are several ways to continue research in this direction. The NJL model has already been studied in many variations, e.g., by adding further degrees of freedom, such as a vector-channel interactions and Polyakovloop dynamics [23,[32][33][34], or by including finite quarkmass effects [35] and considering isospin-asymmetric matter [20,36]. All these extensions could in principle also be studied together with color superconductivity.…”
Section: Resultsmentioning
confidence: 99%
“…A similar description might also be possible by using the on-shell effective field theory that was recently proposed in Ref. [55].…”
Section: Theoretical Frameworkmentioning
confidence: 95%